Pituitary-Adrenal Axis Responses to Routine Management Procedures in Sheep (Ovis aries) - Fazio, Esterina; Medica, Pietro; Cravana, Cristina; Ferlazzo, Adriana (Acta Scientiae Veterinariae, 2016)
Background: Shearing is considered as a stressful factor in sheep, capable of causing some behavioural changes including variations of body condition and hormonal and haematochemical parameters. On these basis, circulating ACTH and cortisol concentrations were determined in sheep before and after exposure to aversive stimuli in order to evaluate the potential use of these hormones to objectively measure physical and mental stress responses to isolation, restraint and shearing. Materials, Methods & Results: Forty Pinzirita sheep, used as experimental group, were evaluated in baseline conditions, 24 h before isolation, restraint and shearing (T0), after isolation (T1), after restraint and shearing (T2), by taking into account the influence of previous shearing experience (just shorn). A control group of forty sheep (intact) was evaluated in baseline condition (T0). According to previous experience the experimental subjects were divided in two groups, respectively group A represented by 20 sheep (10 males and 10 females), aged 1-2 years, without previous shearing experience (intact); and group B represented by 20 sheep (10 males and 10 females), aged older than 2 years, previously exposed to shearing (just shorn). A control group C of 40 sheep splitted into two sub-groups represented by 10 intact males and 10 intact females, aged 1-2 years, and 10 males and 10 females just shorn, aged older than 2 years, was evaluated in baseline conditions (T0). Blood samples were collected 24 h before experimental practices (T0: 08:00 h), after 1 h after of isolation (T1) and after restraint and shearing, around an average of 5 min (T2). All samples were taken in quiet conditions by the same operator. Serum ACTH concentrations were assayed by a commercial radioimmunoassay (RIA). Serum cortisol concentrations were assayed by amplified Enzyme Immunoassay (EIA). Two-way RM ANOVA showed a significant effect of husbandry procedures on ACTH changes, with higher ACTH and cortisol concentrations of just shorn than intact males (F = 15.76; P < 0.0001) and females (F = 17.34; P < 0.0005), and on cortisol changes, with higher cortisol concentrations of just shorn than intact males (F = 6.54; P < 0.01) and females (F = 22.66; P < 0.0001). Discussion: The highest ACTH and cortisol values after isolation, with an appreciable increase especially after restraint and shearing in just shorn sheep, showed that the previous shearing exposure could not induce a habituation to the stimulus, probably promoting a larger release of ACTH and cortisol hormones, so inducing an early and marked coping response to stress in just shorn specimens. Thus, it would appear that different ACTH and cortisol responses of sheep with or without previous shearing experience over the study period resulted in some significant differences when exposed to isolation, restraint and shearing, probably due to changes in pituitary-adrenal axis reactivity. Nevertheless, it is possible to interpret the increase in ACTH and cortisol concentrations related to intrinsic endocrine control mechanisms as an increase due to a rise in the stressful stimulus or coping response. The magnitude of ACTH and cortisol changes following isolation, restraint and shearing suggests that measurements of both hormones are useful in assessing husbandry procedures stress in sheep, with marked elevations in just shorn sheep, indicating that experience can induce an early much larger coping response to stressful practice of shearing.